Rudyard Kipling : hell and heroism - Dillingham, William B. (Palgrave Macmillan, 2005)
Rudyard Kipling: Hell and Heroism is an exploration of two fundamental yet greatly neglected aspects of the author's life and writings: his deep-seated pessimism and his complex creed of heroism. The method of the book is both biographical and critical. Biographically, it traces the roots of Kipling's dark worldview and his search for something to believe in, a way of thinking and acting in defiance of life's hellishness. There matters were more basic to him than any of his social or political opinions, but this the first full-length study devoted to them. Critically, the book takes a fresh and close look at some of Kipling's most important works. The result challenges long established assumptions and amounts to a major reconsideration of novels like Kim and stories like "Mary Postgate" and "The Gardener." Central in these discussions of individual writings is Kipling's concern with the heroic life, but of equal importance is the analysis and evaluation of them as works of art. Avoiding the tangled and special language of some recent literary theory, this will appeal to a wide audience of those interested in Kipling's mind and art.